Biocontrol of Penicillium roqueforti on grain - Lillbro, Marie (2006)
The yeast Pichia anomala has been found to inhibit the growth of several mould species. In this paper several mechanisms potentially being the mode of action of the biocontrol yeast P. anomala was examined. P. anomala was compared with a number of yeasts (Pichia farinosa, Clavispora lusitaniae, Pichia guillermondii, Pichia burtonii, an unknown yeast, Hanseniaspora uvarum, Candida fennica, Candida pelliculosa, and Candida silvicola) with respect to four possible mode of actions; killer toxin production, β-1-3-glucanase secretion, production of ethyl acetate and nutrient competition. P. anomala, P. farinosa, C. lusitaniae, P. guillermondii, P. burtonii, C. fennica, C. pelliculosa, and C. silvicola inhibited Penicillium roqueforti growth in a miniature grain silo with moist wheat (water activity of 0.95). The inhibiting effect was enhanced for several of the yeasts when glucose, maltose, glycerol, or starch was added to the miniature silo. The addition of the different carbon sources did not influence the total yeast cell count in the miniature silos, neither was P. roqueforti growth influenced, when cultivated without yeast. P. anomala, C. silvicultrix, P. farinosa, C. lusitaniae, C. silvicola, and C. pelliculosa were found to produce killer toxin against P. roqueforti. Only P. anomala produced any detectable ethyl acetate but due to technical or method problems no conclusions can be drawn from that result. The obtained results did not support killer toxin production, competition for nutrients nor secretion of β-1-3-glucanase as the main mode of action of biocontrol by P. anomala in this grain system. P. farinosa, C. silvicultrix, P. guillermondii, P. burtonii, C. fennica, C. pelliculosa, C. lusitaniae, and C. silvicola are potential biocontrol agents in air tight storage of cereal grain. C. lusitaniae have not been reported to have biocontrol activity earlier.